3D lead-organoselenide-halide perovskites and their mixed-chalcogenide and mixed-halide alloys - Karunadasa, H; Li, J; Wang, Y; Saha, S; Chen, Z; Hofmann, J; Misleh, J; Chapman, KW; Filip, MR; Reimer, JA (Wiley, 2024)
We incorporate Se into the 3D halide perovskite framework using the zwitterionic ligand: SeCYS (+NH3(CH2)2Se-), which occupies both the X- and A+ sites in the prototypical ABX3 perovskite. The new organoselenide-halide perovskites: (SeCYS)PbX2 (X = Cl, Br) expand upon the recently discovered organosulfide-halide perovskites. Single-crystal X-ray diffraction and pair distribution function analysis reveal the average structures of the organoselenide-halide perovskites, whereas the local lead coordination environments and their distributions were probed through solid-state 77Se and 207Pb NMR, complemented by theoretical simulations. Density functional theory calculations illustrate that the band structures of (SeCYS)PbX2 largely resemble those of their S analogs, with similar band dispersion patterns, yet with a considerable bandgap decrease. Optical absorbance measurements indeed show bandgaps of 2.07 and 1.86 eV for (SeCYS)PbX2 with X = Cl and Br, respectively. We further demonstrate routes to alloying the halides (Cl, Br) and chalcogenides (S, Se) continuously tuning the bandgap from 1.86 to 2.31 eV-straddling the ideal range for tandem solar cells or visible-light photocatalysis. The comprehensive description of the average and local structures, and how they can fine-tune the bandgap and potential trap states, respectively, establishes the foundation for understanding this new perovskite family, which combines solid-state and organo-main-group chemistry.